Respuestas
Respuesta dada por:
23
NUMERO = X
![\frac{2x}{3} + 2 = \frac{5x}{6} - 2 \frac{2x}{3} + 2 = \frac{5x}{6} - 2](https://tex.z-dn.net/?f=+%5Cfrac%7B2x%7D%7B3%7D++%2B+2+%3D++%5Cfrac%7B5x%7D%7B6%7D+-+2)
![\frac{2x+6}{3} = \frac{5x-12}{6} \frac{2x+6}{3} = \frac{5x-12}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B2x%2B6%7D%7B3%7D+%3D+%5Cfrac%7B5x-12%7D%7B6%7D+)
En Equis :
6(2x+6) = 3(5x - 12)
12x + 36 = 15x - 36
36 + 36 = 15x - 12x
72 = 3x
x= 24
El numero es 24
En Equis :
6(2x+6) = 3(5x - 12)
12x + 36 = 15x - 36
36 + 36 = 15x - 12x
72 = 3x
x= 24
El numero es 24
Respuesta dada por:
2
Respuesta:
NUMERO = X
\frac{2x}{3} + 2 = \frac{5x}{6} - 2
\frac{2x+6}{3} = \frac{5x-12}{6}
En Equis :
6(2x+6) = 3(5x - 12)
12x + 36 = 15x - 36
36 + 36 = 15x - 12x
72 = 3x
x= 24
Explicación paso a paso:
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
\frac{2x}{3} + 2 = \frac{5x}{6} - 2
\frac{2x+6}{3} = \frac{5x-12}{6}
En Equis :
6(2x+6) = 3(5x - 12)
12x + 36 = 15x - 36
36 + 36 = 15x - 12x
72 = 3x
x= 24